YAP/TAZ: Key Players for Rheumatoid Arthritis Severity by Driving Fibroblast Like Synoviocytes Phenotype and Fibro-Inflammatory Response - Caire, Robin; Audoux, Estelle; Courbon, Guillaume; Michaud, Eva; Petit, Claudie; Dalix, Elisa; Chafchafi, Marwa; Thomas, Mireille; Vanden-Bossche, Arnaud; Navarro, Laurent; Linossier, Marie-Thérèse; Peyroche, Sylvie; et al. (Frontiers in Immunology, 2021)
Objective: The role of YAP/TAZ, two transcriptional co-activators involved in several cancers, was investigated in rheumatoid arthritis (RA). Methods: Fibroblast like synoviocytes (FLS) from patients with RA or osteoarthritis were cultured in 2D or into 3D synovial organoids. Arthritis rat model (n=28) and colitis mouse model (n=21) were used. YAP/TAZ transcriptional activity was inhibited by verteporfin (VP). Multiple techniques were used to assess gene and/or protein expression and/or localization, cell phenotype (invasion, proliferation, apoptosis), bone erosion, and synovial stiffness. Results: YAP/TAZ were transcriptionally active in arthritis (19-fold increase for CTGF expression, a YAP target gene, in RA vs. OA organoids; p<0.05). Stiff support of culture or pro-inflammatory cytokines further enhanced YAP/TAZ transcriptional activity in RA FLS. Inhibiting YAP/TAZ transcriptional activity with VP restored a common phenotype in RA FLS with a decrease in apoptosis resistance, proliferation, invasion, and inflammatory response. Consequently, VP blunted hyperplasic lining layer formation in RA synovial organoids. In vivo, VP treatment strongly reduced arthritis severity (mean arthritic index at 3.1 in arthritic group vs. 2.0 in VP treated group; p<0.01) by restoring synovial homeostasis and decreasing systemic inflammation. YAP/TAZ transcriptional activity also enhanced synovial membrane stiffening in vivo, thus creating a vicious loop with the maintenance of YAP/TAZ activation over time in FLS. YAP/TAZ inhibition was also effective in another inflammatory model of mouse colitis. Conclusion: Our work reveals that YAP/TAZ were critical factors during arthritis. Thus, their transcriptional inhibition could be relevant to treat inflammatory related diseases.